2022
DOI: 10.3390/jcm11010254
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ View of Socio-Medical Care in the Terminal Phase of Amyotrophic Lateral Sclerosis—How Can We Improve Holistic Care in ALS?

Abstract: Multidimensional socio-medical care with an early integration of palliative principles is strongly recommended in amyotrophic lateral sclerosis (ALS), but provided inconsistently. We conducted telephone interviews with 49 former caregivers of deceased ALS patients to examine their experience of care in the terminal phase including caregiver burden. Patients who received specialized palliative care (45% of patients) were more likely to die at home (p = 0.004) and without burdening symptoms (p = 0.021). The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 79 publications
(126 reference statements)
0
22
0
3
Order By: Relevance
“…Although the measurement tools used varied greatly, the most used tool was the Amyotrophic Lateral Sclerosis Functional Rating Scale to measure symptom severity 17,19,20 . These studies showed that both caregivers and care recipients gave similar ratings of the impact of symptom severity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the measurement tools used varied greatly, the most used tool was the Amyotrophic Lateral Sclerosis Functional Rating Scale to measure symptom severity 17,19,20 . These studies showed that both caregivers and care recipients gave similar ratings of the impact of symptom severity.…”
Section: Resultsmentioning
confidence: 99%
“…Better quality of care, in addition to improving end-of-life for people with ALS themselves, would also help reduce the heavy burden on relatives. 27 …”
Section: Discussionmentioning
confidence: 99%
“…[132][133][134] However, the out-of-pocket cost to patients can reach 10s of thousands of dollars a year, and the supportive care burden on family members can be crushing. 135,136 Given those considerations, less than 10% of people with advanced ALS in the U.S. elect to undergo tracheostomy for extended survival. 137 Regardless of indication, tracheostomy is not necessarily irreversible.…”
Section: Tracheostomymentioning
confidence: 99%